1978
DOI: 10.1007/bf00716359
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the menstrual cycle, oral contraception and pregnancy on forearm blood flow, venous distensibility and clotting factors

Abstract: Forearm blood flow, venous distensibility and various clotting factors were determined in 118 apparently healthy women (mean age 26 years), either during the menstrual cycle, or while taking a combined contraceptive (A) with high progestin:estrogen ratio (d-norgestrel 0.125 mg + ethinylestradiol 0.03 mg), or a sequential contraceptive (B) with low progestin: estrogen ratio (megestrol 0.1/1 mg + ethinylestradiol 0.1 mg), or in the 1st, 2nd and 3rd trimester of pregnancy. Venous distensibility in women taking co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
16
1

Year Published

1986
1986
2019
2019

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(18 citation statements)
references
References 27 publications
1
16
1
Order By: Relevance
“…This finding was surprising in light of previous research in which most (1,7,10,22,23,40) but not all (6) studies have shown that variations in exogenous and endogenous forms of the female sex hormones change the distensibility of the veins.…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations
“…This finding was surprising in light of previous research in which most (1,7,10,22,23,40) but not all (6) studies have shown that variations in exogenous and endogenous forms of the female sex hormones change the distensibility of the veins.…”
Section: Discussionmentioning
confidence: 69%
“…tive use (7,10) and pregnancy (1,7,10,23). However, Duncan et al (6) found no difference in the distensibility of the veins during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the presence of this phenomenon in quadrupedal animals might point to a different aetiology. Venous capacitance is increased in pregnancy (Fawer, Dettling, Weihs, Weltl & Schelling, 1978) possibly due to the effects of elevated levels of circulating progesterone (Fawer et al 1978). After the abrupt offest of exercise with the loss of the peripheral 'muscle pump' aiding venous return, venous blood might have a greater tendency to pool peripherally.…”
Section: Discussionmentioning
confidence: 99%